The Focal easy guide to Premiere Pro : for new users and professionals - Kolb, Tim (Focal easy guide series., 2004)
In this book the author "shares his professional insight to ensure you get the most out of all the tools Adobe's Premiere Pro offers. All the essential areas are covered: set-up, capture, editing, audio, effects and working with Photoshop, After Effects and Encore. Featured are many workflow tips that show how to tap into the full power of Premiere Pro creating you own digital movies."--Back cover